Compatible interaction of Brachypodium distachyon and endophytic fungus Microdochium bolleyi. - Pavel Matušinsky; Božena Sedláková; Dominik Bleša (PLoS ONE, 2022)
Brachypodium distachyon is a useful model organism for studying interaction of cereals with phytopathogenic fungi. The present study tested the possibility of a compatible interaction of B. distachyon with the endophytic fungus Microdochium bolleyi originated from wheat roots. There was evaluated the effect of this endophytic fungus on the intensity of the attack by pathogen Fusarium culmorum in B. distachyon and wheat, and also changes in expression of genes (in B. distachyon: BdChitinase1, BdPR1-5, BdLOX3, BdPAL, BdEIN3, and BdAOS; and in wheat: TaB2H2(chitinase), TaPR1.1, TaLOX, TaPAL, TaEIN2, and TaAOS) involved in defence against pathogens. Using light microscopy and newly developed specific primers was found to be root colonization of B. distachyon by the endophyte M. bolleyi. B. distachyon plants, as well as wheat inoculated with M. bolleyi showed significantly weaker symptoms on leaves from infection by fungus F. culmorum than did plants without the endophyte. Expression of genes BdPR1-5, BdChitinase1, and BdLOX3 in B. distachyon and of TaPR1.1 and TaB2H2 in wheat was upregulated after infection with F. culmorum. M. bolleyi-mediated resistance in B. distachyon was independent of the expression of the most tested genes. Taken together, the results of the present study show that B. distachyon can be used as a model host system for endophytic fungus M. bolleyi.